Review evolution of dual-resource-constrained scheduling problems in manufacturing systems: modeling and scheduling methods’ trends - Delgoshaei, Aidin; Mohd Ariffin, Mohd Khairol Anuar; Maleki, Sepehr; Leman, Zulkiflle (Springer Verlag, 2023)
Dual-resource-constrained scheduling problems (DRCSP) have been hotly debated during the last two decades. DRCSPs focus on the causes and consequences of problems arising from improper simultaneous planning of human resources and machines in various industrial sectors, yielding decreasing productivity of industrial factories. This research focuses on time-oriented problems (including makespan, setup, transportation), cost-oriented problems (including execution cost, workforce salary, raw material, maintenance, and repair), workforce-oriented problems (salary, homogeneous workers, overload workers, aged workers, mobile workers) and performance and energy problems in DRCSPs. To this end, special attention is given to the root and reasons for emerging significant issues, such as the lack of machines, system imbalance, material transferring, bottleneck machines, voids, and human resource over-allocation that usually happens during the scheduling of dual-resource-constrained systems. For this purpose, an in-depth analysis has been conducted by reviewing 122 dominant research papers available in the literature from 2006 to 2022. The advantages, limitations, and significant drawbacks of scheduling DRC problems have been discussed for each studied case. This study’s results clarified gaps to be addressed in studied areas of DRCSP, showing that various aspects of workforce, energy, and performance should receive more attention in future research. A list of directions for future research is provided at the end of the paper.